CHRONIC KIDNEY DISEASE AND FATAL OUTCOMES IN PATIENTS HOSPITALIZED DUE TO TYPE 2 DIABETES IN BELGRADE DURING 2019 - Stefanovic, Nemanja (HEALTH CARE, 2022)
Introduction/Aim: Chronic kidney disease (CKD) is an important complication of type 2 diabetes (T2D), which can lead to further deterioration of health in T2D patients. The aim of this study was to examine whether there is a significant difference in dying, as well as in relation to age and gender, between patients with and without chronic kidney disease (codes: N18.1 -N18.9) hospitalized because of T2D. Methods: The total of 1983 hospital admission episodes that occurred in 2019 in Belgrade, and met the designated selection criteria, were selected from the database maintained by the Institute of Public Health of Belgrade. The preparation and statistical analysis of database was done with the help of software package IBM SPSS Statistics for Windows version 26 (IBM Corp., Armonk, N.Y., USA). Results: Fatal outcomes were significantly more frequent (p = 0.038) in the group with at least one of diagnoses N18.1-N18.9, compared to the comparison group (4.8% vs. 2.1%). The patients in group with at least one of diagnoses N18.1-N18.9 were on average 7.42 years older (p < 0.001), compared to the comparison group. The occurrence of hospital admission episodes with at least one of diagnoses N18.1-N18.9, was significantly more frequent (p = 0.006) in males compared to females (5.5% vs. 4.0%). Conclusion: Further research in this area is necessary, which can contribute to reducing the consequences caused by these conditions - both those that directly affect the health of patients, and the overall burden on the health system, which is reflected in the determined higher costs and longer duration of hospital treatment of patients with T2D if these patients also suffer from CKD.